The Effect of Peer Tutor Method on Learning Outcomes Mathematics at Private Junior High School PTPN 4 Mayang - Situmorang, Radika; Prasetia, Indra (Lembaga Riset Mutiara Akbar, 2022)
The formulation of the problem in this study is whether there is an effect of the Peer Tutor method on students' mathematics learning outcomes at PTPN 4 Mayang Private Junior High School. This study aims to determine the effect of the Peer Tutor method on students' mathematics learning outcomes at PTPN 4 Mayang Private Junior High School. The sample in this study were students of class VIII-C, amounting to 27 people. This type of research is quantitative research with a pre-experimental design type One Group Pretest-Posttest. The research instrument used a description test with SPLDV material. The data collection technique used an initial test (pre-test) and a final test (post-test). The data analysis technique used prerequisite tests (normality test and homogeneity test) and hypothesis testing. The results of the study used a paired sample t test using SPSS Statistics 22 which resulted in a significance of 0.000 < 0.05, also using manual calculations tcount > ttable with df = n-1, namely 37,158 > 2,056 so that Ha was accepted and H0 rejected. It can be concluded from the hypothesis test that students' mathematics learning outcomes after the peer tutoring method is applied are better than the previous method.